The effect of a short, animated story-based video on COVID-19 vaccine hesitancy: a study protocol for an online randomized controlled trial - Barteit, Sandra; Hachaturyan, Violetta; Beleites, Ferdinand; Kühn, Tilman; Favaretti, Caterina; Adam, Maya; Bärnighausen, Till (Frontiers in Public Health, 2022)
IntroductionExposure to a high volume of vaccine misinformation on social media can have a negative effect on vaccine confidence and rates. To counteract misinformation, we designed a collage of three short, animated story-based (SAS) videos to convey scientifically informed and accessible information about COVID-19 vaccine applicable to a social media context.Methods and analysisWe will conduct an online randomized controlled trial primarily to: (1) determine the effectiveness of SAS videos in improving COVID-19 vaccine knowledge; (2) evaluate the effectiveness of SAS videos in increasing behavioral intent for COVID-19 vaccination; and (3) quantify people's interest in watching SAS videos about the COVID-19 vaccine. We also aim to identify barriers and facilitators to COIVD-19 vaccinations that have been shown to minimize vaccine hesitancy between vaccinated and unvaccinated populations. Using a web-based recruitment platform, a total of 10,000 adults from the United States will be recruited and randomly assigned to (1) a SAS video collage arm, (2) an attention placebo control video arm, or (3) no intervention arm (1:1:1). Furthermore, we will measure behavioral intent to obtain information on vaccination regarding COVID-19. At the end of the trial, participants randomized to arm 2 and arm 3 will be given the option of watching one of the intervention videos voluntarily to assess participant engagement with SAS videos. Finally, we will assess individual factors associated with vaccine hesitancy - hope, optimism, COVID-19 perceived risks and benefits, self-efficacy, perceived social norms, and trust - and compare vaccinated and unvaccinated participants across the three arms.DiscussionsEvidence-based information from official channels can be complex and inaccessible to the general public, whereas false information on social media is frequently shared in brief postings, images, or videos that can easily reach the general public, thereby rapidly disseminating (mis-)information. To avoid the spread of misinformation, social media may be used to deliver evidence-based and emotionally compelling information in a readily accessible format in order to pre-empt misinformation. Our findings may help inform future SAS efforts addressing COVID-19 and other important public health challenges.Ethics and disseminationThe study was approved by the Heidelberg University Hospital's Ethics Committee (S-163/2022). The trial was registered with German Clinical Trials Register (www.drks.de) on 5 January 2022: number DRKS00027938. Findings of the study will be published in peer-reviewed scientific publications and possibly presented at scientific conferences.
Gesehen am 12.12.2022